Agroinfection as an alternative to insects for infecting plants with beet western yellows luteovirus. - Leiser, R M (1992)
Beet western yellows luteovirus, like other luteoviruses, cannot be transmitted to host plants by mechanical inoculation but requires an aphid vector, a feature that has heretofore presented a serious obstacle to the study of such viruses. In this paper we describe use of agroinfection to infect hosts with beet western yellows virus without recourse to aphids. Agroinfection is a procedure for introducing a plant virus into a host via Agrobacterium tumefaciens harboring a Ti plasmid, which can efficiently transfer a portion of the plasmid (T-DNA) to plant cells near a wound. The viral genome must be inserted into the T-DNA in such a way that it can escape and begin autonomous replication, a requirement that has, so far, limited agroinfection to pathogens with a circular genome. We have cloned cDNA corresponding to the complete beet western yellows virus RNA genome between the cauliflower mosaic virus 35S promoter and the nopaline synthase transcription termination signal. In one construct, a self-cleaving (ribozyme) sequence was included so as to produce a transcript in planta with a 3' extremity almost identical to natural viral RNA. When inoculated mechanically to host plants, the naked plasmid DNA was not infectious but, when introduced into T-DNA and agroinfected to plants, both the construct with and without the ribozyme produced an infection. This approach should be applicable to virtually any plant virus with a linear plus-strand RNA genome.